2009
DOI: 10.1111/j.1651-2227.2009.01417.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification, incidence and survival analyses of children with CNS tumours diagnosed in Sweden 1984–2005

Abstract: The mean annual incidence of children with CNS tumours was 4.2/100,000 and has not increased during the study period. Survival rate for brain tumours at 10 years follow-up was 72%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
97
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 26 publications
19
97
3
1
Order By: Relevance
“…In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years. We did however observe a doubling of the risk of death for those aged under 5 years, consistent with other studies (3,5,(15)(16)(17)(18)(19)31) due to treatment strategies for infants and young children that defer or avoid radiation (7).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years. We did however observe a doubling of the risk of death for those aged under 5 years, consistent with other studies (3,5,(15)(16)(17)(18)(19)31) due to treatment strategies for infants and young children that defer or avoid radiation (7).…”
Section: Discussionsupporting
confidence: 91%
“…Central nervous system (CNS) tumours are the second most common site of neoplasms diagnosed in children, accounting for approximately one quarter of all childhood cancers (0-14 years), (1) and 14% of tumours diagnosed in teenagers and young adults (TYA) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years) (2). They are the most common cause of cancer related death in children and TYA (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnostic information of the Swedish (Lannering et al, 2009) and most of the Danish cases (Thorsteinsson et al, 2005;RaaschouNielsen et al, 2006) was reabstracted and recoded on the basis of information from individual medical records. In Finland, pathology reports were consulted to classify glia cell tumours more specifically than the data available from the Finnish Cancer Registry.…”
Section: Methodsmentioning
confidence: 99%
“…Another study in Italy showed the incidence of brain tumour was 40 per million children per year 3 . In Sweden a study showed annual incidence of childhood brain tumour was 42 per million children of less than 15 years 4 . Another study in Japan showed age adjusted annual incidence rate of primary intracranial tumour was 36.1 per million children 5 .…”
Section: Introductionmentioning
confidence: 99%